Characterization of the Akirin Gene and Its Role in the NF-κB Signaling Pathway of Sogatella furcifera - Chen, Jing; Zhang, Dao-Wei; Jin, Xing; Xu, Xian-Lin; Zeng, Bo-Ping (Frontiers in Physiology, 2018)
Akirin is an essential nuclear protein involved in the regulation of NF-κB signaling pathway. In most invertebrates, Akirin regulates NF-κB-related Imd and Toll pathways; however, in Drosophila, it only controls the Imd pathway, whereas its role in NF-κB signaling pathway in other insect species is unclear. In the present study, we used white-backed planthopper Sogatella furcifera as a model to investigate the functional activity of Akirin in insects. The sequence of Akirin cDNA was extracted from transcriptome database of S. furcifera; it contained a 585 bp open reading frame encoding a putative protein of 194 amino acids. S. furcifera Akirin (SfAkirin) had a molecular weight of about 21.69 kDa and a theoretical pI of 8.66 and included a nuclear localization signal (NLS) of five amino acid residues at the N-terminal region. Evolutionary analysis showed that SfAkirin was evolutionary closer to Akirins of such relatively distant species as crustaceans than to those of some insect orders like Diptera and Hymenoptera. Tissue-specific expression analysis showed that the SfAkirin gene was expressed in all examined tissues, with the highest expression levels detected in the testis, followed by the ovary, whereas the lowest expression was found in the head. Real-time quantitative PCR analysis showed that SfAkirin mRNA was strongly induced in response to injection of heat-inactivated Escherichia coli and Bacillus subtilis, whereas SfAkirin silencing by RNA interference significantly reduced the expression of NF-κB dependent transcription factors Dorsal and Relish after B. subtilis and E. coli challenge, respectively. Our results suggest that SfAkirin may control the immune response of S. furcifera against bacterial infection via both Imd and Toll signaling pathways.